2014
DOI: 10.1007/s10549-014-3141-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of metformin on breast cancer proliferation according to markers of insulin resistance and tumor subtype in a randomized presurgical trial

Abstract: Treatment of diabetics with metformin is associated with decreased breast cancer risk in observational studies, but it remains unclear if this drug has clinical antineoplastic activity. In a recent presurgical trial, we found a heterogeneous effect of metformin on breast cancer proliferation (ki-67) depending upon insulin resistance (HOMA index). Here, we determined the associations of additional serum biomarkers of insulin resistance, tumor subtype, and drug concentration with ki-67 response to metformin. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 49 publications
4
44
0
Order By: Relevance
“…2.8 under metformin, in line with our prior observation in invasive cancer (10), although this finding was based on eight cases only. These results extend and further complement our prior findings in HER2þve invasive disease, where metformin significantly reduced the Ki-67 increase observed in the placebo arm after 4 week between biopsy and surgery (15,34). In addition, the number of adjacent HER2þve DCIS was larger than that of HER2þve invasive cancer, in line with prior data (35), indicating that our findings do not simply replicate results in HER2þve invasive disease (15).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…2.8 under metformin, in line with our prior observation in invasive cancer (10), although this finding was based on eight cases only. These results extend and further complement our prior findings in HER2þve invasive disease, where metformin significantly reduced the Ki-67 increase observed in the placebo arm after 4 week between biopsy and surgery (15,34). In addition, the number of adjacent HER2þve DCIS was larger than that of HER2þve invasive cancer, in line with prior data (35), indicating that our findings do not simply replicate results in HER2þve invasive disease (15).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, metformin selectively decreased Ki-67 LI in HER2þve cancers and in women with additional markers of insulin resistance (15). In the present study, we show the high prevalence of the field cancerization effect, with a 70% prevalence of intraepithelial neoplastic lesions in tissue surrounding invasive cancers, supporting the notion that the presurgical model may be a cost effective model to screen agents with preventive potential.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, our study failed to support that possibility: results were similar when insulin users were excluded. Furthermore, there is evidence that metformin is associated with a greater reduction in tumour growth in individuals who attain the largest reduction in insulin level 29 . Thus, metformin's effect might be lost when not accounting for varying levels of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Also the increased risk of cancer-related death in diabetic patients who have used sulfonylureas and exogenous insulin was much more significant in comparison with metformin users (15). Clinical evidences have suggested that metformin could prevent proliferation and growth of certain types of cancers, such as breast cancer, even in absence of diabetes (16). According to the above results about the efficacy of metformin in treatment and prevention of breast cancer death; in comparison with other medicines such as sulfonylureas, it would be necessary to perform a metaanalysis in related research of metformin effects on prevention and treatment of breast cancer The results of this study could be the basis for making beneficial therapeutic purposes in prevention, treatment and reducing the effects of breast cancer, such as breast cancer mortality.…”
Section: Contextmentioning
confidence: 99%